Pembelajaran Fardu Kifayah dalam Materi PAI: Tinjaun atas Manuskrip Risālat Al-Tahjīz Karya H. Muhammad Jabir Sambas (1872-1947) - Sahrul Sobirin; Erwin Mahrus (Universitas Muhammadiyah Prof Dr Hamka, 2023)
This study aims to identify the manuscript of Risālat al-Tajhīz, by H. Muhammad Jabir, a scholar from Sambas, West Kalimantan, then see its relevance to PAI materials in schools, especially fardu kifayah. This study is a qualitative research using two approaches, namely library research and historical research. This study concludes that the Risālat al-Tajhīz manuscript is one of the important works produced by local scholars of West Kalimantan. Judging from its structure, the al-Tajhīz manuscript is more detailed in the description and steps of the management of the corpse complete with the legal basis that accompanies it. In other words, the material in Risalat al-Tajhiz is very relevant so that it can be used as an alternative companion book to enrich PAI teaching materials delivered to students